2015
DOI: 10.7755/fb.113.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors driving the density of derelict crab pots and their associated bycatch in North Carolina waters

Abstract: Abstract-Lost or derelict fishing gear can impair fisheries by contributing to the depletion of target species populations and can reduce nontarget fish and wildlife populations. We measured the density of derelict crab pot (DCPs) using side-scan sonar and examined bycatch associated with DCPs in nearshore waters (depths ≤4 m) of 6 waterbodies important to the North Carolina blue crab fishery, the state's most valued commercial fishery. Extrapolated mean DCP density was 105 DCP/km 2 of open water (range: 6-301… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Several past studies have identified the direct loss of biomass in the population of target species (e.g., blue crab, Dungeness crab Cancer magister) due to ghost fishing mortalities by derelict pots over time (Breen 1987, Guillory 1993, Havens et al 2008, Giordano et al 2010, Antonelis et al 2011, Anderson and Alford 2014, Bilkovic et al 2014, Voss et al 2015. For example, bycatch mortality of blue crabs in derelict pots is estimated at 20-26 crabs per pot per year (Guillory 1993, Giordano et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Several past studies have identified the direct loss of biomass in the population of target species (e.g., blue crab, Dungeness crab Cancer magister) due to ghost fishing mortalities by derelict pots over time (Breen 1987, Guillory 1993, Havens et al 2008, Giordano et al 2010, Antonelis et al 2011, Anderson and Alford 2014, Bilkovic et al 2014, Voss et al 2015. For example, bycatch mortality of blue crabs in derelict pots is estimated at 20-26 crabs per pot per year (Guillory 1993, Giordano et al 2010.…”
Section: Introductionmentioning
confidence: 99%